OPTIMIZING PERSONAL IMAGE: QUANTITATIVE CHANGES IN THE HAIR AND MAKEUP MODIFICATION - Zabora, Volodymyr (Theory and practice of design, 2023)
The aim of this study is to uncover the alterations in personal image that arise from individual modifications of hairstyle and makeup. The research methodology deployed involves a comprehensive review of quantitative studies pertaining to hairstyle and makeup modifications, thereby reflecting the socio-psychological transformations experienced by the individual. An axiomatic approach is adopted for the thorough analysis of secondary sources. The novelty of this research lies in its synthesis of psychological and aesthetic results derived from facial style design through makeup and hairstyling. This study highlights the multi-dimensional impact of non-invasive face modification methods, which significantly influence an individual’s overall image and self-efficacy. Explorations within the domain of psycho-aesthetics are crucial for comprehending a stylistic decision as a conscious and effective choice. A holistic perspective in understanding personal image considers not only physical transformations, but also the related psychological and sociocultural consequences, thereby expanding traditional discourse within the design field. In conclusion, enhancing one’s self-image through non-invasive practices of altering facial style, such as makeup application and hairstyling, sets the stage for a profound transformation of the individual’s image. These seemingly superficial interventions wield a significant impact on the individual’s identity, altering their embodied existence and context of self-presentation. The relevance of the «Less is more» aesthetic medicine paradigm is underscored, serving as a foundation for aestheticization and effective self-expression. The pivotal role of personal image modification techniques, such as makeup and hairstyling, in shaping an individual’s internal and perceived identity is emphasized. The influence of these techniques extends beyond mere stylistic choices, spotlighting the significant repercussions of even the subtlest aesthetic adjustments on self-perception and societal perceptions. This article accentuates the necessity for a comprehensive understanding of these non-invasive personal image modification practices.